the 3rd answer should be the correct one
Answer:
Option A is correct
Step-by-step explanation:
For the box y=mx+c
Hope this helps
Answer:
x = 3, y = 1 is the solution of the given system.
Step-by-step explanation:
Here, the given system of equations is:
y = -x + 4 ...... (1)
y = x - 2 .......... (2)
Now, to find the solution of the system, SUBSTITUTE the value of y from equation (1) in to the equation (2). We get ,
y = x - 2 ⇒ -x + 4 = x - 2 ( as from (1), y = -x + 4)
or, -x -x = -2 -4
or, - 2 x = -6 ⇒ x = 6/2 = 3
or, x = 3
⇒ y = x - 2 = 3 - 2 = 1
⇒ y = 1
Hence, x = 3, y = 1 is the solution of the given system.
Answer:
Step-by-step explanation:
Change mixed fraction to improper fraction. Then reduce to lowest term if possible.
6 1/4 x 3 3/5 = 25/4 * 18/5 = 25* 18 /4*5
= 5 * 18 / 4 {giving by 5th table}
= 5* 9 /2 { giving by 2nd tables}
= 45/2